Complex Roles of CpG in Liposomal Delivery of DNA and Oligonucleotides. Issue 2 (April 2002) - Wilson, Annette; Pitt, Bruce; Li, Song
Abstract : Unmethylated CpG in bacterial DNA has recently been recognized as a danger signal to the mammalian immune system. This CpG signal can be greatly amplified when DNA is delivered via a lipidic vector. The CpG effects are affected by the administration route, and can be either beneficial or harmful. In this review, we will summarize our current understanding about the mechanism of action of the immunostimulatory motifs. Emphasis will be placed on the discussion of the complicated roles of CpG when CpG DNA or oligonucleotides are administered in vivo using liposomes as a delivery vehicle.